CARBON DIOXIDE EMISSION FACTOR ESTIMATION FROM INDONESIAN COAL - Retno Damayanti; Herni Khaerunissa (Indonesian Mining Journal, 2018)
Climate change will become the priority for the air quality management. It focuses more on carbon dioxide emission. Indonesia which has power generation dominated by coal combustion is expected to develop the national CO2 emission factor. Due to the high variation in Indonesia coal rank and its growing magnitude in CO2 emission caused by the future coal-fired power plant development, the characteristic emission value becomes an important concern. The method used in this study is developed from the IPCC Guidelines for Energy. The conversion unit plays an important role in the calculation method. The result shows that the higher in C content, the lower in its CO2 emission factor. It means that coal classified as high C content or high heating value will produce low carbon dioxide emission factor. The average CO2 emission factor obtained in Indonesian coal is 99,718 kg CO2/TJ with an average value of carbon content 27.2 kg C/GJ, and NCV equal to 19.8 TJ/Gg. Coal rank is categorized as lignite to subbituminous or bituminous.